COMPARISON BETWEEN INDONESIAN GOVERNMENT POLICIES AND TAIWAN IN FACING THE COVID-19 PANDEMIC AT TIRTO.ID POSTER - Hafidz Ridha Try Sjahputra; Nisa Adzkiya (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2021)
The COVID-19 pandemic captured the attention of all media, not least Tirto.id who uploaded a poster on his Instagram feed exactly the first 30 days of COVID-19 in Indonesia. The poster discusses taiwan's handling of the situation in his country. So it raises the question Tirto.id chose Taiwan to fill its posters? Using van Dijk's critical discourse analysis to see the power at play behind the Tirto.id posters, as well as to dialogue the rational actor model I put forward by Graham to compensate for the policies and regulations imposed by the Governments of Indonesia and Taiwan in the handling of pandemics in their respective countries. Produce findings namely; First, Tirto.id praised taiwan's successful handling of the pandemic as well as a relaxed form of sarcasm to the Government of Indonesia during the first 30 days. Second, historically, Taiwan's past failures with the SARS epidemic have made them learn to be better prepared from many sides. Meanwhile, Indonesia's success in handling Bird Flu makes Indonesia more relaxed and optimistic in the face of this pandemic.